2019
DOI: 10.21608/ijhms.2019.119040
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cultural Awareness towards Heritage Sites among Local Communities for Sustainable Tourism Development “The case of Qaitbay Castle in Alexandria”

Abstract: Qaitbay Castle is one of the most important heritage sites in Alexandria which has recently witnessed many negative practices. Therefore, this study evaluates the level of cultural awareness of residents in Qaitbay Castle area. It also investigates their gains from tourism advantages, as well as their participation in heritage preservation which helps achieving sustainable tourism development. The study was conducted through two methods: (1) interviews with managers in some tourism and heritage official instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The oral interview thus show that the residents of Idanre Community are highly aware of the festivals being celebrated annually on Idanre Hills. Firma et al (2021) however reported moderate awareness of cultural festival among the residents while Kamel (2019) reported low level of awareness of cultural festivals. The key informants also stated their sources of awareness of the festivals celebrated on the hills:…”
Section: Socio-demographic Characteristics Of the Touristsmentioning
confidence: 99%
“…The oral interview thus show that the residents of Idanre Community are highly aware of the festivals being celebrated annually on Idanre Hills. Firma et al (2021) however reported moderate awareness of cultural festival among the residents while Kamel (2019) reported low level of awareness of cultural festivals. The key informants also stated their sources of awareness of the festivals celebrated on the hills:…”
Section: Socio-demographic Characteristics Of the Touristsmentioning
confidence: 99%
“…Alexandria was founded by Alexander the Great in 331 BC, since then it became the capital of the Egypt until the early Islamic period (Ragheb, 2014;Lasaponara et al, 2017;Kamel, 2019).…”
Section: Archaeological Sites In Alexandriamentioning
confidence: 99%
“…The Citadel of Qaitbay: The Qaitbay fortress in Alexandria was known as one of the most important Islamic monuments in Alexandria (Kamel, 2019;Ragheb, 2014). The constructions work lasted two years, from 882-1477 to 884-1479 (Pradines, 2016) by the Sultan Al Ashraf Qaitbay Mamlouke in the place of the famous ancient Alexandria lighthouse on the eastern point of Pharos Island (Kamel, 2019) to protect the city and to ensure the safe passage of the ships in the harbors (Pradines, 2016). Thus, it has an important location on the entrance to Alexandria's eastern harbor (Darwish, 2018;Kamel, 2019).…”
Section: Archaeological Sites In Alexandriamentioning
confidence: 99%